(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Manual library record-keeping often leads to misplaced records, slow book searching, inaccurate borrower tracking, and difficulty in monitoring available and borrowed books. To address these problems, this study developed Efficient Record-Keeping: A GUI-Based Python Library Management System, a desktop-based application designed to help manage library book records and borrowing transactions in a faster, more organized, and more accurate way. The system was developed using Python as the main programming language, a graphical user interface for user interaction, and SQLite as the database management system for permanent record storage. The system includes essential library management features such as adding book records, viewing available books, searching book information, editing book details, deleting records, borrowing books, returning books, and generating reports. Through database integration, book and borrower records remain saved even after the program is closed. The system also reduces manual work by allowing users to retrieve records quickly and update book status efficiently. Overall, the developed Library Management System provides a practical and user-friendly solution for improving library record-keeping, book monitoring, and borrowing management.